Albania : Technical Assistance Report-Tax Policy Reform Options for the MTRS. (IMF Staff Country Reports; Country Report ;, 2022)
Albania is preparing a Medium-Term Revenue Strategy (MTRS) to finance its development spending of an estimated 2.2-3.0 percent of GDP over five years. Revenue mobilization will be supported by comprehensive tax policy and administration reforms. International and regional comparisons suggest that there is room for additional revenues as well as improvement in the composition of tax revenues. This report presents options for tax policy reform to raise at least an additional 1.34 percent of GDP in revenues over five years and to improve the quality and efficiency of the tax system, that will enable the mobilization of further domestic revenues.